Preliminary characterization and ecotoxicity assessment of paperboard industry waste - Silva, Nádia da; Niemeyer, Júlia Carina; Stolberg, Joni (Revista de Ciências Agroveterinárias, 2020)
Paper and paperboard industry generate solid waste that demands correct treatment or disposal. The objective of this work was to characterize the solid waste of two paperboard industries located in Santa Catarina and to assess its ecotoxicity. The characterization involved the determination of moisture, ashes, and cellulose content. Ecotoxicity tests included avoidance behavior tests with earthworms (Eisenia andrei), reproduction tests with collembolans (Folsomia candida), and a test of germination and growth of roots of lettuce (Lactuca sativa). Results of the ecotoxicity tests were assessed using ANOVA followed by tests of Tukey and Dunnett and Fisher exact test (p<0.05). Wastes 1 and 2 presented moisture of 87.23 and 60.80%, ashes 11.18 and 55.12%, and cellulose 59.34 and 66.78%, respectively. Avoidance and reproduction tests did not indicate ecotoxicity for earthworms and collembolans when compared to the soil from pinus plantation. Concerning lettuce root growth, Waste 1 showed toxicity for the concentrations of 100, 75, and 50% of its elutriate. The results indicated that the wastes have chemical, physical, and ecotoxicological characteristics that may be restrictive for their application on agricultural soils.